Generalized Common Fixed Point Result in Banach Space - Jha, Kanhaiya (Journal of Nepal Mathematical Society, 2018)
The aim of this paper is to establish a common fixed point theorem for weakly compatible pair of self mappings in Banach space which generalizes and improves various well known comparable results.